2002
DOI: 10.1074/jbc.m200002200
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of the Class II Peroxidases, Lignin Peroxidase andArthromyces ramosus Peroxidase, with Hydrogen Peroxide

Abstract: The reactions of the fungal enzymes Arthromyces ramosus peroxidase (ARP) and Phanerochaete chrysosporium lignin peroxidase (LiP) with hydrogen peroxide (H 2 O 2 ) have been studied. Both enzymes exhibited catalase activity with hyperbolic H 2 O 2 concentration dependence (K m Ϸ 8 -10 mM, k cat Ϸ 1-3 s ؊1 ). The catalase and peroxidase activities of LiP were inhibited within 10 min and those of ARP in 1 h. The inactivation constants were calculated using two independent methods; LiP, k i Ϸ 1 The heme peroxidase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(23 citation statements)
references
References 40 publications
2
20
1
Order By: Relevance
“…In this study, we used label-free quantitative liquid chromatography mass spectrometry (Label-free LC-MS/MS) to analyze protein expression in the kidneys of control rats and hyperuricemic rats that were treated with SGR. Of the differentially expressed proteins, catalase is noteworthy because it is responsible for the degradation of hydrogen peroxide [16], and it is a protective enzyme that is present in nearly all animal cells [17,18,19]. In this study, we also demonstrated that catalase could be upregulated by SGR and that it reduced the generation of ROS that were induced by high concentrations of uric acid in vitro .…”
Section: Introductionsupporting
confidence: 57%
“…In this study, we used label-free quantitative liquid chromatography mass spectrometry (Label-free LC-MS/MS) to analyze protein expression in the kidneys of control rats and hyperuricemic rats that were treated with SGR. Of the differentially expressed proteins, catalase is noteworthy because it is responsible for the degradation of hydrogen peroxide [16], and it is a protective enzyme that is present in nearly all animal cells [17,18,19]. In this study, we also demonstrated that catalase could be upregulated by SGR and that it reduced the generation of ROS that were induced by high concentrations of uric acid in vitro .…”
Section: Introductionsupporting
confidence: 57%
“…Two main reaction pathways, comprising catalase and peroxidase activities, have been distinguished for classical peroxidases (e.g., horseradish peroxidase) in the absence of reducing substrates (Hiner et al, 2002;Ruiz et al, 2001 (Kadima et al, 1994), and Compound III was detected with UV-Vis spectroscopy in the presence of excess H 2 O 2 (Lambeir and Dunford, 1985;Nakajima et al, 1985). Moreover, CPO inactivation by H 2 O 2 at pH 4.1 (Fig.…”
Section: Discussion Reaction Pathway Of Cpomentioning
confidence: 98%
“…Thus, the data in Figure 3 between t ¼ 0 and 2.5 min indicate that the average specific H 2 O 2 removal rate at pH 4.1 (47,000 mmol H 2 O 2 /mmol CPO/min) was 7.5% higher than at pH 6.0. A greater rate of H 2 O 2 removal indicates higher peroxidase activity because three molecules of H 2 O 2 are consumed within a cycle of the peroxidase pathway, whereas only two molecules of H 2 O 2 are consumed in the catalase pathway (Hiner et al, 2002;Ruiz et al, 2001).…”
Section: Effect Of Ph On Cpo Inactivation By Oxidantsmentioning
confidence: 97%
See 1 more Smart Citation
“…These data are undiminished by the supposed methodological problems raised by Dr Baldrian; while veratryl alcohol is commonly used, it is untrue that 2,2-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid is not a suitable substrate (e.g. Hiner et al 2002;Gerini et al 2003). Similarly, while it may be theoretically true that the assay for endocellulase reXects cumulative cellulase activities, this is clearly not the case here.…”
Section: Ecological Relevance Of Secreted Enzymes For Em Fungimentioning
confidence: 99%